2014
DOI: 10.1093/nar/gku496
|View full text |Cite
|
Sign up to set email alerts
|

GtrS and GltR form a two-component system: the central role of 2-ketogluconate in the expression of exotoxin A and glucose catabolic enzymes inPseudomonas aeruginosa

Abstract: In the human pathogen Pseudomonas aeruginosa, the GltR regulator is required for glucose transport, whereas GtrS is a sensor kinase that plays a key role in mediating bacteria–host interaction and pathogen dissemination in the host. We show that GtrS and GltR form a two-component system that regulates the expression from the promoters Pedd/gap-1, PoprB and Pglk, which control the expression of genes involved in glucose metabolism and transport. In addition, the GtrS/GltR pair regulates the expression of toxA t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 48 publications
1
48
0
Order By: Relevance
“…The genes encoding the carbohydrate catabolic pathways are organized in operons (Fig. ), which are under the control of different regulators that respond differentially to distinct pathway intermediates, suggesting a hierarchy in the control of glucose metabolism related to a tight gene expression (Rojo, ; Daddaoua et al ., ; Figs and ).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The genes encoding the carbohydrate catabolic pathways are organized in operons (Fig. ), which are under the control of different regulators that respond differentially to distinct pathway intermediates, suggesting a hierarchy in the control of glucose metabolism related to a tight gene expression (Rojo, ; Daddaoua et al ., ; Figs and ).…”
Section: Introductionmentioning
confidence: 90%
“…However, Daddaoua et al . () demonstrated that the GltR and GtrS form indeed a TCS. GtrS is a transmembrane sensor kinase that contains a periplasmic ligand binding domain.…”
Section: Transcriptional Regulators Involved In Pseudomonas Carbohydrmentioning
confidence: 96%
“…This motif composition differs from canonical histidine kinase proteins. Canonical histidine kinase typically has an additional two motifs including the HAMP motif [histidine kinase, adenylyl cyclase, methyl-accepting protein and phosphatase (PF00672)] which is a phosphoacceptor domain that acts as a cytoplasmic intermediate linker connecting the phosphoryl transfer (HisKA) motif [68,[70][71][72][73][74] with the sensor domains outside of cytoplasm [70,75,76]. Biochemical characterization of the G3 Hyd in A. woodii indicates that it forms a tetrameric complex that includes HydBC and a Fd-like HydD protein that contains a [2Fe-2S] cluster [21].…”
Section: Taxonomic Distribution and Classification Of Hyda Homologsmentioning
confidence: 99%
“…Using microcalorimetry and EMSA the binding affinities of different effectors to the PtxS, HexR and GtrS regulators have been determined (Daddaoua et al ., ). In all cases derived constants were in the micromolar range.…”
Section: Discussionmentioning
confidence: 97%